Impact of Oxidative Stress on Risk of Death and Readmission in African Children With Severe Malaria: A Prospective Observational Study. (9th June 2022) - Blatt, Daniel B; Hanisch, Benjamin; Co, Katrina; Datta, Dibyadyuti; Bond, Caitlin; Opoka, Robert O; Cusick, Sarah E; Michelow, Ian C; John, Chandy C
Abstract: Background: We hypothesized that oxidative stress in Ugandan children with severe malaria is associated with mortality. Methods: We evaluated biomarkers of oxidative stress in children with cerebral malaria (CM, n = 77) or severe malarial anemia (SMA, n = 79), who were enrolled in a randomized clinical trial of immediate vs delayed iron therapy, compared with community children (CC, n = 83). Associations between admission biomarkers and risk of death during hospitalization or risk of readmission within 6 months were analyzed. Results: Nine children with CM and none with SMA died during hospitalization. Children with CM or SMA had higher levels of heme oxygenase-1 (HO-1) ( P < .001) and lower superoxide dismutase (SOD) activity than CC ( P < .02). Children with CM had a higher risk of death with increasing HO-1 concentration (odds ratio [OR], 6.07 [95% confidence interval CI, 1.17–31.31]; P = .03) but a lower risk of death with increasing SOD activity (OR, 0.02 [95% CI, .001–.70]; P = .03). There were no associations between oxidative stress biomarkers on admission and risk of readmission within 6 months of enrollment. Conclusions: Children with CM or SMA develop oxidative stress in response to severe malaria. Oxidative stress is associated with higher mortality in children with CM but not with SMA. Clinical Trials Registration: NCT01093989. Abstract : African children with cerebral malaria (CM) or severe malarial anemia (SMA) develop oxidative stress in response to severe malaria. Oxidative stress is associated with higher mortality in children with CM but not with SMA, and has no impact on readmission.